معيقات استعمال التعليم الاليكتروني من وجهة نظر تدريسيي معهد الفنون الجميلة (Journal of the College of Basic Education, 2022)
The aim of the research is to identify (obstacles to the use of e-learning from the point of view of the teachers of the Institute of Fine Arts). In order to identify these obstacles, the researcher formulated two null hypotheses:1 - There are no statistically significant differences on the average scores of the teachers of the Institute of Fine Arts, according to the gender variable, on the items of the e-learning Obstacles Questionnaire.2 - There are no statistically significant differences on the average scores of the teachers of the Institute of Fine Arts, according to the educational qualification variable, on the paragraphs of the e-learning obstacles questionnaire.The research community consisted of a total of (488) teachers of the Institutes of Fine Arts in the city of Baghdad. The researcher chose her research sample in a simple random way. The sample size amounted to (82) male and female teachers who obtained bachelor’s, master’s and doctoral degrees, with (41) teachers holding bachelor’s degrees and (41) teachers holding master’s and doctoral degrees. The researcher built the research tool (the questionnaire) from (19) paragraphs, and after obtaining validity and reliability, it was applied to the basic research sample. After using the statistical bag, the results of the obstacles appeared on all the paragraphs of the questionnaire, and there were differences towards the male sample of teachers according to the hypothesis of the gender variable. As for the hypothesis of the educational qualification variable, it showed differences in favor of teachers with bachelor's degrees